2011
DOI: 10.1002/ppap.201000168
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Microbiological Characterisation of Staphylococcus epidermidis Inactivation by Dielectric Barrier Discharge Plasma

Abstract: The inactivation of the Gram‐positive bacteria Staphylococcus epidermidis (ATCC 12228) in its vegetative state was studied in vitro after exposure to cold atmospheric pressure plasma generated by direct dielectric barrier discharge (DBD). Compared to UV radiation at 254 nm, plasma UV emission yielded no significant contribution to bacterial inactivation. Analysis of bacterial growth inhibition revealed a pH dependency on growth media. Yet, measurements combined with numerical simulations excluded the pH shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…The gram‐negative bacteria E. coli and P. aeruginosa and the yeast C. albicans showed a different pattern of damage after the plasma treatment than the gram‐positive bacteria S. epidermidis does. The latter did not show any morphological change after the plasma treatment . On the one hand, a reason might be that the cell wall consisting of peptidoglycans is much stronger and, thus, can be more than ten times thicker than a gram‐negative cell wall.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The gram‐negative bacteria E. coli and P. aeruginosa and the yeast C. albicans showed a different pattern of damage after the plasma treatment than the gram‐positive bacteria S. epidermidis does. The latter did not show any morphological change after the plasma treatment . On the one hand, a reason might be that the cell wall consisting of peptidoglycans is much stronger and, thus, can be more than ten times thicker than a gram‐negative cell wall.…”
Section: Resultsmentioning
confidence: 94%
“…The antiseptic efficacy of direct plasma generated by a dielectric barrier discharge (DBD) on gram‐positive Staphylococcus epidermidis has already been studied and was published in a previous paper . To broaden the database of the microorganisms investigated, the antiseptic efficacy on gram‐negative bacteria ( Escherichia coli and Pseudomonas aeruginosa ) and on yeast ( Candida albicans ) was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma induced UV intensities and thermal impact on the bacteria can be neglected. Thus, the major cause of cell death in this study is due to the membrane damage induced by cold plasma treatment (34). The results of OES indicated that the reactive oxygen species, especially oxygen, was generated and led to oxidative stress and cell damage, which are the key inactivation agents in cold plasma (35).…”
Section: Discussionmentioning
confidence: 97%
“…The synergistic effect of the plasma treatment, such as sterilization, increase in microcirculation, and skin acidification provides the advantage of using plasma over, for example, pulse electric field or phototherapy. [ 91–96 ] Further research focused on understanding the effect of plasma at either the level of individual molecules or at the cellular level. For example, plasma can induce a biologically relevant modification in proteins, [ 97 ] DNA, [ 98 ] and amino acids.…”
Section: Transport Of Reactive Agentsmentioning
confidence: 99%